HUBUNGAN PENGEMBANGAN KARIER DAN LOYALITAS GURU DI MADRASAH TSANAWIYAH NEGERI 1 KOTA PEKANBARU - Darna, Yusni - (Journal of Education and Teaching, 2022)
Every madrasa principal wants a teacher who is qualified and professional in carrying out his duties and is loyal to him. This loyalty will foster positive attitudes where the teacher works. If loyalty has been built, the results will be very good because this loyalty will be able to form a psychological relationship between teachers and madrasas. Many factors are thought to cause the high and low teacher loyalty. One of them is career development. Therefore, one of the principal's efforts to increase teacher loyalty is through career planning and development. The relationship between career development and teacher loyalty at Madrasah Tsanawiyah Negeri 1 Pekanbaru City shows a positive relationship. This means that teacher loyalty can be increased through career development, if career development is carried out as optimally as possible. The implementation of career development will be effectively carried out if the madrasah pays attention to the needs of teachers, such as providing opportunities for teachers to continue their study programs at a higher level, conducting continuous training so that teachers are increasingly able to teach and educate well. Keywords: Teacher, Loyalty and CareerABSTRAKSetiap kepala madrasah menginginkan gurunya yang berkualitas dan profesional dalam menjalankan tugas dan loyal kepadanya. Loyalitas ini akan menumbuhkan sikap-sikap yang positif dimana tempat guru tersebut bekerja. Jika loyalitas sudah terbangun maka hasilnya akan sangat baik karena loyalitas ini akan mampu membentuk hubungan kejiwaan antara guru dan madrasah. Banyak faktor yang diduga menyebabkan tinggi rendahnya loyalitas guru. Diantaranya adalah pengembangan karier. Karena itu salah satu upaya kepala madrasah untuk meningkatkan loyalitas guru adalah dengan melalui perencanaan dan pengembangan karier. Adapun hubungan pengembangan karier dan  loyalitas guru di Madrasah Tsanawiyah Negeri 1 Kota Pekanbaru menunjukkan hubungan yang positif. Artinya loyalitas guru dapat ditingkatkan melalui pengembangan karier, apabila pengembangan karier dilaksanakan seoptimal mungkin. Pelaksanaan pengembanagan karier akan efektif dilakukan apabila pihak madrasah memperhatikan kebutuhan guru seperti, memberikan kesempatan kepada guru untuk melanjutkan program studi kejenjang yang lebih tinggi, melakukan pelatihan-pelatihan yang berkesinambungan sehingga guru semakin mampu mengajar dan mendidik dengan baik. Kata Kunci: Guru, Loyalitas dan Karier